PROFIL KETERAMPILAN DAN SIKAP SOSIAL MELALUI TUGAS PROYEK PADA PESERTA SM3T-UR TAHUN 2013-2014 DI KABUPATEN LANNY JAYA PAPUA - Yustina ' ' (Biogenesis, 2015)
This descriptive study was conducted in November 2013 to August 2014, aims to evaluate the project work skills and social attitudes through Project-Based Learning (Pj-BL) in SM3T participants Lanny Jaya district. This study used a total sampling technique involving 32 teachers SM3T-UR, and distributed 4 to 5 people per district on the 7 district. Parameters consisted of: a. skills tasks and projects with components of each item: 1) preparation (design, schedule, coordination of activities); 2) implementation (suitability of activities, suitability schedules, documentation, licensing and constraints); 3) The product that report and essay stori with the assessment format, content, systematic writing, documentation); b. Social attitudes includes honesty, discipline, responsibility, polite, caring and confident). The data of skills collected in the form of reports and stori, then analyzed using pothpolio sheet. Social attitudes data were collected using a sheet of self-assessment questionnaires and peer assessment questionnaire. Data were analyzed by determining a score, percentage and tabulated, and then analyzed descriptively. Results of the study found Skills project tasks in 6 districts Lanny Jaya categorized Good, and the district excellent categorized, is participants of Nokapaka district. Component lowest skill district is implementing a project on the item suitability with the implementation of planning activities, suitability with the implementation of the planned schedule and constraints in implementation in categorize Quite. Reporting skills and overall stori work items categorized Good. Social attitudes of participants SM3T-UR in the monitoring-1 are likely lower than the monitoring-2. Lowest social attitudes in the monitoring-1 is confident, meanwhile the lowest monitoring-2 is the attitude of caring and polite. Social attitudes of participants Very Good is in Makki districtand Nokapaka district. Conclusion is skills of project task and social attitudes of participants SM3T-UR categorized Good. From the project task, we can concluse that Pj-BL can aim the profile skill and social attitude from SM3_T participants.Keywords : Project-Based Learning, Skills project task, Social attitudes, SM3T Program.